Morphosyntactic Translation Strategies and Contextual Meanings of "Surah Al-Baqarah" Verse 45 Based on Peter Newmark's Theory - Akmal Tastary; Muhammad Kholil; Sultan Abdurrafi; Ekawati Mughni (Litteratura: Jurnal Bahasa dan Sastra, 2026)
The morphological and morphosyntactic translation strategies of Surah Al-Baqarah Verse 45 and its contextual meaning are analyzed in this study based on Peter Newmark’s theory, focusing specifically on literal and communicative strategies. The data are sourced from the Quranic text and the digital translation of NU Online. Employing a qualitative descriptive method with a content analysis technique, the research identifies linguistic units across morphological aspects (wasta'īnū), syntactic aspects (the prepositional letter ب in biṣ-ṣabr; the istitsnā' structure in illā 'alā al-khāshi'īn), and semantic-rhetorical aspects (the emphatic particles innā and the emphatic lām in lakabīrah), subsequently classifying them into Newmark’s categories of translation methods and procedures. The findings indicate that the translator selectively combines literal and communicative methods through procedures such as modulation, explicitation, and amplification on elements experiencing meaning shifts due to Arabic morphosyntactic structures. These findings confirm that the morphosyntactic complexity and rhetorical functions of the Arabic language determine the selection of translation strategies for Quranic verses. This research contributes by offering an analytical model for translation strategies at the morphological and syntactic levels that can be applied to other verses with similar linguistic structures. Regarding contextual meaning, Surah Al-Baqarah verse 45 offers a comprehensive psychological-spiritual formula for humans to overcome life's pressures through the synergy between patience as internal self-regulation and prayer as an anchor of spiritual communication. Keywords: Quranic Translation, Translation Strategies, Peter Newmark's Theory, Morphosyntax, Contextuality of Meaning.